Կոմիտասի թանգարան-ինստիտուտի ինտերիերի դիզայնը - Անի Աճառյան (ՀՀ ԳԱԱ հրատ.)
В статье анализируются основные черты дизайна интерьера Музея-института Комитаса. В систематическом порядке представлены тематические экспозиции музея по планам.The article analyzes the main features of the interior design of the Komitas Museum-Institute. In classified order presented are themed expositions of the Museum by layouts.
Keywords: Fine Arts; Architectural Drawing and Design